Liquid‐Phase Transmission Electron Microscopy for Studying Colloidal Inorganic Nanoparticles. Issue 4 (27th November 2017) - Kim, Byung Hyo; Yang, Jiwoong; Lee, Donghoon; Choi, Back Kyu; Hyeon, Taeghwan; Park, Jungwon
Abstract: For the past few decades, nanoparticles of various sizes, shapes, and compositions have been synthesized and utilized in many different applications. However, due to a lack of analytical tools that can characterize structural changes at the nanoscale level, many of their growth and transformation processes are not yet well understood. The recently developed technique of liquid‐phase transmission electron microscopy (TEM) has gained much attention as a new tool to directly observe chemical reactions that occur in solution. Due to its high spatial and temporal resolution, this technique is widely employed to reveal fundamental mechanisms of nanoparticle growth and transformation. Here, the technical developments for liquid‐phase TEM together with their application to the study of solution‐phase nanoparticle chemistry are summarized. Two types of liquid cells that can be used in the high‐vacuum conditions required by TEM are discussed, followed by recent in situ TEM studies of chemical reactions of colloidal nanoparticles. New findings on the growth mechanism, transformation, and motion of nanoparticles are subsequently discussed in detail. Abstract : Liquid‐phase transmission electron microscopy (TEM) is gaining much attention as a new tool to directly observe chemical reactions that occur in solution. The technical developments for liquid‐phase TEM and their application to the study of solution‐phase nanoparticle chemistry are summarized.